Rosin building at Hercules Brunswick plant - Hercules Incorporated (1960)
Exterior view of a rosin manufacturing facility at the Hercules Powder Company plant in Brunswick, Georgia with view of digesters on right-hand side. One of two Hercules plants specializing in naval stores, the Brunswick plant extracted rosin, turpentine, and pine oil from pine tree stumps in order to produce a range of chemicals used in the manufacture of varnishes, paints, adhesives, insecticides, textiles, and other industrial products. The employees visible in the photograph are identified as operator James Altman (left), pipefitter Elbert Ogden (at work bench), and Herman Wood (with wheelbarrow). Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Naval stores industry; Employees; Chemical industry; Hercules Incorporated; Corporations; Naval stores